The Influence of the Problem Based Learning Model on Critical Thinking Ability and Learning Motivation in Islamic Religious Education of Class X - Indra Prabowo; Yuberti; Agus Jatmiko (Bulletin of Pedagogical Research, 2025)
The ability to think critically and motivate students to learn in Islamic Religious Education (PAI) learning is one of the abilities students need to support them in solving problems in PAI lessons. Based on pre-research results, students' critical thinking skills and learning motivation are still low; apart from that, there is a lack of variety in the learning models used. To overcome this problem, researchers used the PBL learning model. This research aims to determine the effect of the PBL learning model on students' critical thinking abilities and learning motivation. This research is research (Quasi-Experimental Design). The sampling technique uses the Cluster Random Sampling technique. The sample in this research was class X (TKR) students as the experimental class and class X (TKJ) as the control class. The instruments used to collect data are tests and questionnaires. The data analysis techniques used are the normality test, homogeneity test, and hypothesis testing using the MANOVA test. Based on the MANOVA test, the values obtained from Pillai's Trace, Wilks' Lamda, Hotelling's Trace, Roy's Largest Root = 0.000, and α test criteria = 0.05, which means the p-value value is smaller than α test criteria, so H_0 is rejected. Thus, it can be concluded that the PBL learning model influences students' critical thinking abilities and learning motivation.